Patriarchy and Paternalistic Culture of Religious Leader Deification Causing Sexual Harassment in Islamic Educational Institutions - Razak, Abd; Nuraini, Nuraini; Putra, Rahmad Syah; Kurniawan, Rahmat (el Harakah: Jurnal Budaya Islam, 2024)
The rise of sexual harassment perpetrated by religious figures in Islamic educational institutions has raised doubts about the role and objectives of these institutions in Aceh. This research aims to determine how sexual harassment is influenced by religious culture and the impact of such cases on the image of Islamic educational institutions. It is qualitative-descriptive in nature. Data were collected using observation, interviews, and documentation instruments. Meanwhile, data analysis was carried out using descriptive analysis. The results show that cult-like practices contribute to sexual harassment in Islamic educational institutions as part of the religious culture within these institutions. The strength of these cult practices, as part of the religious culture, is intertwined with the role of patriarchal culture and paternalistic leadership deeply rooted in society. This harassment occurs through the abuse of religious dogma, such as the method of transferring metaphysical knowledge. With the continued increase in cases of sexual harassment within Islamic educational institutions, parents have grown doubtful about the educational process in institutions run by religious figures, leading them to prefer general educational institutions instead. This finding is helpful for understanding the causes and methods of preventing the recurrence of sexual harassment in Islamic educational institutions. Maraknya pelecehan seksual yang dilakukan oleh tokoh agama di lembaga pendidikan Islam telah menimbulkan keraguan tentang peran dan tujuan lembaga-lembaga tersebut di Aceh. Penelitian ini bertujuan untuk menentukan bagaimana pelecehan seksual dipengaruhi oleh budaya agama dan dampak kasus-kasus tersebut terhadap citra lembaga pendidikan Islam. Penelitian ini bersifat kualitatif-deskriptif. Data dikumpulkan menggunakan instrumen observasi, wawancara, dan dokumentasi. Sementara itu, analisis data dilakukan menggunakan analisis deskriptif. Hasil penelitian menunjukkan bahwa praktik-praktik seperti sekte berkontribusi terhadap pelecehan seksual di lembaga pendidikan Islam sebagai bagian dari budaya agama dalam lembaga-lembaga tersebut. Kekuatan praktik-praktik sekte ini, sebagai bagian dari budaya agama, terkait erat dengan peran budaya patriarki dan kepemimpinan paternalistik yang sangat tertanam dalam masyarakat. Pelecehan ini terjadi melalui penyalahgunaan dogma agama, seperti metode transfer pengetahuan metafisik. Dengan terus meningkatnya kasus pelecehan seksual di lembaga pendidikan Islam, orang tua semakin meragukan proses pendidikan di lembaga-lembaga yang dijalankan oleh tokoh agama, sehingga mereka cenderung memilih lembaga pendidikan umum. Temuan ini berguna untuk memahami penyebab dan metode pencegahan berulangnya pelecehan seksual di lembaga pendidikan Islam.